Determination of selected fatty acids in dried blood spot by gas chromatography-flame ionization detection - Andrlová, Lenka; Řeháková, Zuzana; Kanďár, Roman (My University, 2017)
With the aim to minimize the amount of biological material needed for analysis, a new type of sample preparation has been used for the determination of the percentage content of fatty acids in human blood. The blood samples from the volunteers (n = 30) were processed in two ways, as a plasma and as dried blood spot (DBS) samples. The fatty acids were firstly derivatized into the respective esters and, subsequently, separated and detected using gas chromatography (GC) with a flame ionization detector (FID). The results obtained from the DBS sample analysis were compared with those obtained by the established method for the determination of fatty acids in plasma.
Stanovení vybraných mastných kyselin v suché kapce krve plynovou chromatografií s plamenoionizační detekcí
Keywords: fatty acids; gas chromatography with flame ionization detection; dried blood spot; mastné kyseliny; plynová chromatografie s plamenoionizačním detektorem; suchá kapka krve